Transcription and processing of a yeast tRNA gene containing a modified intervening sequence - Johnson, Jerry D. (Proc Natl Acad Sci U S A, 1980)
The tRNA(3)(Leu) gene from yeast contains an intervening sequence of 32 nucleotides not present in mature tRNA. This sequence is transcribed and subsequently removed during the maturation of the RNA. To probe the involvement of this region of the gene in transcription and processing of the pre-tRNA(3)(Leu), the yeast DNA was cloned in plasmid pBR322 and a 21-base-pair DNA fragment corresponding to the lac operator was inserted into the intervening sequence. Insertion was done at a cleavage site for the restriction endonuclease Hpa I that occurs 19/20 base pairs from the 5′ end of the intervening sequence. The parent and modified plasmids were then transcribed in a Xenopus germinal vesicle extract. RNA-fingerprint analysis of the transcription products revealed that both the tRNA(3)(Leu) gene and its modified counterpart were accurately transcribed. Transcription products corresponding to mature tRNA(3)(Leu) and pre-RNA(3)(Leu) with the normal and lac-containing intervening sequence were identified. Precursors extended at their 5′ and 3′ ends were also present. Both parent and modified genes were transcribed efficiently, and the various products accumulated in similar amounts, indicating that no deleterious effects on transcriptional competence, stability of the transcripts, or processing result from insertion of the 21-base-pair lac operator DNA. Incubation of pre-tRNA molecules that contained intervening sequences but were 5′ and 3′ mature with a yeast ribosomal wash fraction resulted in excision of the intervening sequence and, in the presence of ATP, ligation of the resulting half-tRNA molecules. The presence of RNA complementary to lac operator DNA neither inhibited the excision and splicing activities nor altered the site of the junction. IMAGES: